2022
DOI: 10.22225/seas.6.2.5730.94-101
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Strategy of Honey in Sarining Trigona Pertiwi Beekeeper Bongkasa Pertiwi Village

Abstract: Honey bees are one of the potential forest resources to be developed and cultivated. Marketing is an important part of business development. The purpose of this study is to identify of factors that affect honey business cultivation and to obtain the strategy for business development of the business Trigonola Laevicep honey in Sarining Trigona Pertiwi. The method used in this research is the descriptive method using questionnaire, observation, interview, and documentation. The data found were analyzed using des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…According to [7], [8], [9] marketing is very important to do because it is a very important activity to be able to introduce a product or service widely and thoroughly so that it can be known to the general public. The results of research by [10] external factors that influence opportunities for honey business development in the Sarining Trigona Pertiwi Badung group are the creation of promotional media through social media and online marketing. Research results [11], [12] found that failure in the product marketing process was due to the fact that the products being sold were not widely known, limited distribution reach, and intense competition between similar products.…”
Section: Introductionmentioning
confidence: 99%
“…According to [7], [8], [9] marketing is very important to do because it is a very important activity to be able to introduce a product or service widely and thoroughly so that it can be known to the general public. The results of research by [10] external factors that influence opportunities for honey business development in the Sarining Trigona Pertiwi Badung group are the creation of promotional media through social media and online marketing. Research results [11], [12] found that failure in the product marketing process was due to the fact that the products being sold were not widely known, limited distribution reach, and intense competition between similar products.…”
Section: Introductionmentioning
confidence: 99%